Inhibitors performance in CO2 corrosion EIS studies on the interaction between their molecular structure and steel microstructure - López, D.A. (2005)
The performance of three imidazoline-like inhibitors in CO2 corrosion was studied by means of electrochemical measurements employing a.c. and d.c. techniques. Carbon steel with two different microstructures (annealed, and quenched and tempered (Q&T)) was used in a deoxygenated 5% wt. NaCl solution, saturated with CO2 at 40 °C and pH 6. Aminopropylimidazol (API) and two commercial imidazoline-based products (PC and QB) were used as inhibitors. Electrochemical impedance spectroscopy (EIS) and linear polarization resistance (LRP) studies showed that the annealed samples have a better corrosion resistance than the Q&T samples when API and PC were added. On the other hand, the presence of QB yielded the opposite results. From the Bode phase angle plots it can be concluded that in the first case and for both microstructural conditions, there is no indication of formation of an inhibitor film, whereas in the presence of QB its formation is clearly evident. Based on these experimental findings, a mechanism of action for each inhibitor is proposed.